2019
DOI: 10.1007/s11548-019-01913-5
|View full text |Cite
|
Sign up to set email alerts
|

Interactive virtual 3D models of renal cancer patient anatomies alter partial nephrectomy surgical planning decisions and increase surgeon confidence compared to volume-rendered images

Abstract: PurposeTo determine whether the interactive visualisation of patient-specific virtual 3D models of the renal anatomy influences the pre-operative decision-making process of urological surgeons for complex renal cancer operations.MethodsFive historic renal cancer patient pre-operative computed tomography (CT) datasets were retrospectively selected based on RENAL nephrectomy score and variety of anatomy. Interactive virtual 3D models were generated for each dataset using image segmentation software and were made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…As indicated by the results of previous studies, the present study underlines how use of the appropriate imaging tool is fundamental for precise evaluation of the tumour anatomical complexity in preoperative planning, potentially influencing the intervention strategy as well as the surgical indication [32,33].…”
Section: Discussionmentioning
confidence: 73%
“…As indicated by the results of previous studies, the present study underlines how use of the appropriate imaging tool is fundamental for precise evaluation of the tumour anatomical complexity in preoperative planning, potentially influencing the intervention strategy as well as the surgical indication [32,33].…”
Section: Discussionmentioning
confidence: 73%
“…As a surgical navigator, a 3Dprinted kidney model can reduce image distortion and enable accurate tumour positioning [12]. However, due to the limitations in this kind of study design, no studies have objectively proved these advantages, as the vast majority of studies have been performed in the areas of surgical planning, [11,[15][16][17][18][19][20][21]. Thus, elucidating the advantages in surgical effectiveness is of paramount importance.…”
Section: Discussionmentioning
confidence: 99%
“…They found the benefits of a 3D-VR model in renal function preservation and postoperative complications. Hyde et al [21] used preoperative interactive 3D-VR models for surgical planning in 25 surgeons. They found that the application of the 3D-VR models resulted in a 19% change in the planned surgical approach and increased surgeon confidence in the surgical decisions in four/five patient datasets.…”
Section: Several Previous Studies Have Reported Console-integrated Realtime 3d Image-only Navigation (Virtual Reconstruction [Vr]mentioning
confidence: 99%
“…Out of the 37 studies analyzed, twenty-three reported the usefulness and applications of virtual and printed 3D kidney models in "surgical planning" and "surgical training". Fourteen [36][37][38][39][40][41][42][43][44][45][46][47][48][49] of these were crosssectional studies, mainly surveying the impact of 3D models in understanding renal anatomy and renal tumor by young surgeons, medical students and patients. Table I is a summary of study characteristics of the use of 3D VR models in renal tumors.…”
Section: Study Characteristicsmentioning
confidence: 99%